Sustainable Design for Environmental Disaster - Chia, Wee Khuan (Universiti Teknologi PETRONAS, 2018)
Earthquakes are one of the major environmental disaster which affect people worldwide and becoming more intense as the years go on. On January 12th, 2010, a point 15km southwest of Port-Au-Prince was struck by an earthquake of Magnitude 7.0 which leads to more than 230,000 deaths and significant buildings destruction. In 2011, another earthquake of 9.0 Magnitude struck the Tohoku City, Japan which consequently triggered the tsunami and the explosion of the nuclear power plant in Fukushima, causing unprecedented damage. The recovery process from the aftermath of both devastating incidents were endless and posed great economic impacts to the country. In the recent years, Malaysia started experiencing earthquakes and lately, on March 9th, 2018, a 5.2 Magnitude earthquake jolted Ranau, Sabah, which raises insecurities and critical concern from the civilians. As a result, seeking protective measures for earthquakes becomes highest priority to minimize the damage and risk.